Research of textile logarithmic-aperiodic antennas with a matching circuit for textronics applications - Frydrysiak, Michal Pawel (Textile research journal, 2022)
The antenna is the basic element of radio communication systems. Its proper design allows for a sufficiently wide transmission range and quality of data transmission. Most known communication systems operate in a certain frequency range and dipole antennas only work at one frequency of resonance, therefore log-aperiodic antennas are built for covering a wide bandwidth. In a typical configuration, such antennas are made of metal rods; however, in textronics garment applications a flat structure integrated with the textiles is necessary. This article presents the construction and research of a flat antenna entirely made with textile materials and with the use of technologies. Embroidery technology was proposed for the prototyping of antennas for all three communication technologies. Polyester multifilament yarns with a silver top layer were used in the research. A textile impedance matching circuit for the antenna was also built with the use of textile technology. The antennas were designed for the Global System for Mobile Communications, Global Positioning System and WiFi systems, because such wireless technologies have been used in the prototype system for transmitting measurement data of human physiological signals in textronics clothing. Wearable antennas are a part of a device that ensures continuous health monitoring of an elderly person or a patient without hindering his day-to-day activities. The construction of this system was the subject of a project financed by the National Centre for Research and Development in Poland. The design stage was presented along with the method of connecting the antenna with the transmitter. The repeatability of the antenna parameters was also analyzed and a textile impedance matching circuit was presented. In this article, the author focused on checking the quality and repeatability of electrical and geometric parameters of textile antennas for various types of transmission, including connections in constant environmental conditions.